A dark and stormy night - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries, 2010)
When Dorothy Martin and her husband, retired Chief Constable Alan Nesbitt, are invited to a country house weekend, they expect nothing more explosive than the Guy Fawkes fireworks. Having read every Agatha Christie ever written, Dorothy should have known better. Rendered isolated and incommunicado by the storm, Dorothy and Alan nevertheless manage to work out what in the world has been happening at ancient Branston Abbey.